Histopathological Profile of Pediatric Solid Malignant Neoplasm in Tertiary Care Centre - Ayesha, Syeda; Sonwane, Bharat R (Annals of Pathology and Laboratory Medicine, 2020)
Background: There is rise in incidence of pediatric tumors all over the globe. In developing country like India childhood morbidity & mortality is mainly due to malnutrition & infections but there is significant rise in incidence of pediatric neoplasm which is now becoming a distinct & important entity to be dealt upon. Objectives: To study the incidence of solid pediatric malignant neoplasms, the age and sex distribution in cases of solid pediatric malignant neoplasms and various histopathological appearance and patterns of solid pediatric malignant neoplasms. Methods: An observational study of solid pediatric malignant neoplasms in childhood was done over a period of 2 years, from November 2016 to October 2018 in the age group of 0-14 years. The institutional ethical committee Government Medical College & Hospital, Aurangabad- Maharashtra India has given approval for this study. Result: Total 180 cases of solid pediatric neoplasm were studied. The total sample received during study period was 180 out of which 55 were malignant. Out of 55 malignant tumors 30 were observed among males and 25 were observed among females. Most of the malignant tumors were observed among 11-14 yrs age group, followed by those observed among 0-3 years. Conclusion: It can be concluded from our study that common solid malignancies in pediatric age group excluding hemato-lymphoid malignancies include nephroblastoma, retinoblastoma, neoplasms of gonads & bone tumors. Male predominance is a salient feature of childhood tumors. Most common solid tumors of childhood originate from embryonal tissue and tumors of epithelial origin are rare. A larger pediatric population based study would provide us with greater insight details about solid pediatric neoplasms.